Princetonians, 1748-1768 : a biographical dictionary - McLachlan, James (Princeton legacy library., 1976)
Benjamin Rush, William Paterson, David Ramsay, Oliver Ellsworth, Jonathan Edwards, Jr.-these are only a few of the remarkable men who attended the College of New Jersey (later Princeton University) in its first twenty-one classes. Alumni included five members of the Constitutional Convention of 1787, twenty two participants in the Continental Congress, four Senators, seven Congressmen, and two Justices of the Supreme Court. This volume describes the lives of the 338 men who graduated from the College between 1748 and 1768. Their biographies are arranged by year of graduation, and an introduction provides the early history of the College and its role in colonial culture. In sharp contrast to the graduates of other colleges at the time, Princeton's early students were either born or found their later careers in every one of the thirteen states as well as in Tennessee, Kentucky, the West Indies, and Ireland. After graduation most became clergymen, lawyers, doctors, businessmen, and soldiers. While some served as national leaders, others rose to prominence in state and local government, becoming governors, state legislators, and participants in the drafting of state constitutions. This record of their lives is a mine of information about America during the Colonial, Revolutionary, and Early National periods.Originally published in 1977.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.